The Popularisation of Football in Spain. An Analysis of the Phenomenon through the Specialised Literature of Football (1920-1936) - Torrebadella i Flix, Xavier; Nomdedeu i Rull, Antoni (Revista General de Información y Documentación, 2016)
The consolidation of football in Spain took place from the 1920s. From 1920 to 1936, football began to acquire all the personal traits that characterise it today. This period gave rise to a specialised technical and journalistic literature that establishes itself as one of the most important pillars for the technical development both of sport and of mass entertainment. With respect to this subject, this article has a double objective: to compile the specialised technical and journalistic literature published from 1920 to 1936, and to recognise the social, technological and ideological impact of this football-related literature on the process of configuring this sport within Spain. To approach these objectives, we have used a methodology that is both heuristic and based on the analysis of original sources. We posit that we will gain, through these works, a far fuller insight into the context of the social-sport aspect of football in Spain and, additionally, that our study will point towards new potential lines of research.